2013
DOI: 10.1083/jcb.201307001
|View full text |Cite
|
Sign up to set email alerts
|

aPKCλ controls epidermal homeostasis and stem cell fate through regulation of division orientation

Abstract: Loss of aPKCλ disrupts epidermal homeostasis and bulge stem cell maintenance by driving cell fate changes via a shift toward asymmetric division

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
109
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(117 citation statements)
references
References 61 publications
7
109
1
Order By: Relevance
“…However, at P4, uniform/bipolar LGN was the predominant localization pattern in OE and headskin. This suggests that there might be a bias toward parallel divisions postnatally, as previously reported in backskin (Niessen et al, 2013) and tail epidermis (Clayton et al, 2007), although it has been reported that 85% of divisions in adult ear epidermis are perpendicular (Lechler and Fuchs, 2005). Similar patterns of LGN were observed at early ( prometaphase) and late (telophase) mitosis, in thin (8 µm) or thick (20 µm) sections ( Fig.…”
Section: Oral Epithelial Development Is Diverse and Dynamicsupporting
confidence: 60%
See 4 more Smart Citations
“…However, at P4, uniform/bipolar LGN was the predominant localization pattern in OE and headskin. This suggests that there might be a bias toward parallel divisions postnatally, as previously reported in backskin (Niessen et al, 2013) and tail epidermis (Clayton et al, 2007), although it has been reported that 85% of divisions in adult ear epidermis are perpendicular (Lechler and Fuchs, 2005). Similar patterns of LGN were observed at early ( prometaphase) and late (telophase) mitosis, in thin (8 µm) or thick (20 µm) sections ( Fig.…”
Section: Oral Epithelial Development Is Diverse and Dynamicsupporting
confidence: 60%
“…In epidermis and HFs lacking Prkcι, a ∼20% increase in perpendicular divisions is observed, leading to prolonged anagen, progressive loss of quiescent bulge HFSCs and, ultimately, hair loss (Niessen et al, 2013). It is presently unknown whether LGN directs these OCDs, although other proteins that colocalize with LGN, including Par3 and NuMA, appear to be expressed normally.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations